Chinese Primary School Students’ Peer Relationship and Chinese Language Scores: The Chain Mediation Effect of Parental Involvement and Sense of Autonomy - Qiu, Huiyan; Chai, Jiang (Frontiers in Psychology, 2022)
This study investigated the internal mechanism of the relationship between primary school students’ peer relationships and their performance in the Chinese language and literature. We constructed a chain mediation model, focused on the mediation effects of parental involvement and the sense of autonomy, on the correlation between peer relationships and performance in Chinese language scores. A questionnaire survey was conducted among 1,503 students in grades 4–6, and their parents, in three cities in Jiangsu Province. The result indicated the following: 1) there was a significant positive correlation between primary school students’ peer relationships, parental involvement, sense of autonomy, and the level of Chinese language scores; 2) parental involvement and the sense of autonomy, respectively mediate the relationship between peer relationships and Chinese language scores; 3) primary school students’ parental involvement and sense of autonomy play a chain-like mediating role in the relationship between their peer relationships and Chinese language scores. The research results provide a reference for exploring the educational strategies of primary school students' Chinese literacy.